The Role of Physical, Sport and Health Education in Developing Healthy Life Behaviors: The Role of Physical, Sport and Health Education in Developing Healthy Life Behaviors - Hidayana, Rizki Apriva (International Journal of Health, Medicine, and Sports, 2023)
Sports education has learning characteristics that are different from other subjects because it is more psychomotor in nature and still involves affective and cognitive abilities that are comparable to learning those who mainly move. Students are expected to be able to improve affective and cognitive skills with learning modifications that have been arranged by the teacher. The same goes for encouraging healthy living habits through sports education. By banning students from the values of healthy living habits, sports education can become the foundation for a complex of knowledge that will help students maintain their quality of life into old age. Health is a fundamental need in life. The majority of individuals frequently disregard the behavior needed to establish a culture of healthy living. To create good quality human beings in terms of physical, mental and spiritual development, it is crucial to promote a culture of healthy living. The government and people who care about health must continue to step up their efforts to better understand each person in order to develop a perspective that can shift behavior in a positive direction. It is believed that through physical, sports and health education in educational institutions, children will develop a healthy lifestyle culture from an early age.